الرؤيا وأفق الكتابة بين التجربتين الصوفية والشعرية قراءة تحليلية في كتابات حركة شعر (El-Wahat Journal for Research and Studies, 2017)
This Study Seeks To Uncover The Relationship Between Writing In The Technical Experience And Its Counterpart Mysticism Through The Vision Of The Term, Which Has Become A Link  Point Between The Two Experiments In Contemporary Literature, The Purpose For That  Was The Experience For A Cluster Of Poets Of Poem Movement Which Is Working Hard To Set The Spiritual Nature Of Creativity, And Restore The Relationship Between The L Poet Individuality And His The Work, In Which He  Recalls The Deep Self Experiences And Through Which He Brings Back Via The Language Synonym Of The  Expression And Expressed That From  The Self Point Of View  Emerges The  Expressive Language And From That Vision, The Poet Becomes The Conscience  Of The  Expressed. Keywords  - The Vision ,Escetic, Poem  Movement , Poetic Writing